Interreligious Coexistence in Islam: Implications for Islamic Education and the Achievement of SDGs - Gulzhaina K. Kassymova; Engkizar Engkizar; Mustafa Tevfik Hebebci; Yerassyl K. Talgatov (Muaddib: Journal of Islamic Teaching and Learning, 2025)
The practice of interreligious coexistence in Islam holds significant relevance for Islamic education, particularly in shaping tolerant, just, and inclusive character within multicultural societies. Islam, as a religion that emphasizes peace and justice, provides a normative foundation for curriculum development and educational practices that encourage learners to respect differences, build harmonious relations with adherents of other faiths, and understand the rights and obligations among religious communities. This study aims to analyze the practice of interreligious life from an Islamic perspective with a focus on its implications for Islamic education. Employing a qualitative approach, data were collected from 20 informants consisting of academics, education practitioners, and community leaders through in-depth interviews. The data were analyzed thematically using NVivo 12 software to identify key patterns and themes. The findings reveal four major aspects: respect for each religion’s principles, universal justice without discrimination, inclusive social relations between Muslims and non-Muslims, and equality of rights and obligations among religious groups. The implications highlight that Islamic values can serve as a normative framework for strengthening multicultural-based Islamic education and fostering tolerance, while simultaneously contributing to the achievement of the Sustainable Development Goals (SDGs), particularly quality education (SDG 4), reduced inequalities (SDG 10), peace and justice (SDG 16), and global partnerships (SDG 17).